Pharmacologic management of non-neurogenic functional obstruction in women. (2nd June 2016) - Cohn, Joshua A.; Brown, Elizabeth T.; Reynolds, W. Stuart; Kaufman, Melissa R.; Dmochowski, Roger R.
ABSTRACT: Introduction : Impaired bladder emptying in women without neurologic disease may be related to urethral obstruction and/or impaired bladder contractility. Mechanical obstruction generally requires surgical management and options are limited for impaired bladder contractility. However, functional obstruction from voiding dysfunction or primary bladder neck obstruction may present an opportunity for pharmacologic intervention. Areas covered : In this review, the authors extensively reviewed available literature regarding the use of off-label medications for functional bladder outlet obstruction in women. In addition, side effect profiles and pharmacology of these medications determined from on-label indications are reviewed. Specific medications reviewed include vaginal diazepam, baclofen, urethral botulinum toxin injection, and alpha-adrenergic blockers. Expert opinion : Alpha-blockers in particular have demonstrated promise in women with demonstrable or suspected bladder outlet obstruction with side effect profiles similar to those observed in men. However, lack of quality data hinders informed decision making with alpha-blockers or any of the other agents studied in women with non-neurogenic functional outlet obstruction. In the absence of well-designed, placebo-controlled multi-institutional trials, those prescribing these medications must be aware of special considerations and side effects associated with relatively unfamiliar treatments in the context of uncertain benefit.